2015
DOI: 10.1002/app.43113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen bonding interactions on the properties of ultraviolet‐curable coatings

Abstract: Phenolic novolac type epoxy resin has been modified with acrylic acid (AA) and 2-acrylamido-2-methyl-1propanesulfonic acid (AMPS) to form ultraviolet-curable coatings, and integrated performances of the coatings were evaluated. It was found that the hydrogen bonding interactions among the oligomers became stronger along with the increase of AMPS content, thus the oligomer viscosity and a variety of polymer properties were affected. The polar hydrogen bond donors significantly enhanced the adhesion strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The data of the stress-strain test with the cured resins are listed in Table IV. The specimens were broken without yield and this indicated that the materials were hard and brittle (Shen et al, 2016). As can be seen, in the Figure 7, the tensile strength of EA1, EA2 and EA3 were a little higher than EA.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The data of the stress-strain test with the cured resins are listed in Table IV. The specimens were broken without yield and this indicated that the materials were hard and brittle (Shen et al, 2016). As can be seen, in the Figure 7, the tensile strength of EA1, EA2 and EA3 were a little higher than EA.…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…After immersing in acetone for 48 h, the GCs of these cured materials were calculated and showed in TableI. The value was measured to evaluate the crosslinked molecular structure of the resins (Shen et al, 2016). High GC can be indicated that the polymeric network is tightly crosslinked.…”
Section: Gel Contentmentioning
confidence: 99%